The Strategies For Improving Vocabulary Mastery By The Eighth Year Student at SMP Muhammadiyah 6 Surakarta in 2014/2015 Academic Year - Wahyuni, Riska Tri, Drs. Djoko Srijono, M. Hum, Siti Fatimah S. Pd, M. Hum (2015)
The research studies about the strategy for improving vocabulary mastery done by eighth year students at SMP Muhammadiyah 6 Surakarta. This research describes the strategies for improving vocabulary mastery by the eighth year students of SMP Muhammadiyah 6 Surakarta The type of the research is descriptive method which aims to describe describe the strategies for improving vocabulary mastery by the eighth year students of SMP Muhammadiyah 6 Surakarta. The method of collecting data is observation, interview and documentation. The data are taken from the subject of the research in the form of interview and document. The writer uses Hatch and Brown Theory in analyzing the data. The writer takes three months to collect the data. In three months, they mastered ninety vocabulary. The learning takes place in tutored environment and untutored environment. They use many strategies. The strategies in tutored environment are using power point and picture. While in untutored environment are using memorizing, pictures, watching cartoon film, and song lyric. By using those strategies, they are successful learner.